2010
DOI: 10.5352/jls.2010.20.1.082
|View full text |Cite
|
Sign up to set email alerts
|

Development of Functional Beverage (SanYa) from Fermented Medical Plants and Evaluation of Its Physiological Activities

Abstract: This study was investigated to analyze the contents of flavonoid compounds and the effects of fermentation on the physiological activities of medical plants, also known as SanYa (SY). Antioxidative activity of the fermented SanYa (FSY) was measured by using DPPH radical scavenging and SOD-like activity. DPPH radical scavenging and SOD-like activity of FSY were 94.3% and 45.0%, respectively. Nitric oxide (NO) synthesis was increased 11 times through the addition of FSY. However, NO production of the macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…NO is a reactive nitrogen intermediate produced by macrophages in response to stimulation by cytokines or microorganisms, and is therefore generally considered to be a reliable indicator of macrophage activation. In addition, NO is also involved in immune activation and antioxidant activity by minimizing cytotoxicity caused by cell-activating substances and reactive oxygen intermediates ( Cho et al, 2010 ; Byun, 2013 ). As an active oxygen species, NO is also involved in the regulation of physiological functions including vasodilation, platelet aggregation, and immune response under normal conditions ( Hyun, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…NO is a reactive nitrogen intermediate produced by macrophages in response to stimulation by cytokines or microorganisms, and is therefore generally considered to be a reliable indicator of macrophage activation. In addition, NO is also involved in immune activation and antioxidant activity by minimizing cytotoxicity caused by cell-activating substances and reactive oxygen intermediates ( Cho et al, 2010 ; Byun, 2013 ). As an active oxygen species, NO is also involved in the regulation of physiological functions including vasodilation, platelet aggregation, and immune response under normal conditions ( Hyun, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…또한 항산화 활성을 지닌 원료들은 염증성 질환에도 효과를 보이는데 [1], 면역세포의 nitric oxide synthase (NOS)에서 생 성되며, 외부의 자극에 의해 유전자 수준에서 발현되는 nitric oxide (NO)의 경우 세포 활성화 물질 및 reactive oxygen intermediates (ROI)에 의해 유발된 세포독성을 최소화시킴으로 써 항산화와 더불어 면역 활성 발현에도 관여함이 알려져 있 다 [6]. 항산화 활성이 우수한 물질은 생체 내에서 과도한 외부 Means with different superscripts in the same row (a-d) and column (A-I) are significantly different at p<0.05.…”
Section: 서 론unclassified
“…Je (2015) reported that the important physiological activities of the plant compounds are important anti-inflammatory, anti-hypertensive, and anti-oxidant physiological effects. Recently, the increased interest of the natural substances as an alternative medicine and the market expansion for the tea drinks using health functional extracts have been reported in many researches (Cho et al, 2010;Lee, 2011: Mun et al, 2007Park et al, 2000).…”
Section: Introductionmentioning
confidence: 99%